Effect of pulmonary rehabilitation on heart rate recovery in adult individuals with asthma or chronic obstructive pulmonary disease - Zampogna, Elisabetta; Ambrosino, Nicolino; Oliva, Federico Mattia; Rudi, Monica; Sotgiu, Giovanni; Saderi, Laura; Spanevello, Antonio; Visca, Dina (Frontiers in Pharmacology, 2022)
Introduction. Heart rate recovery (HRR) after exercise is a marker of disease severity and prognosis in cardiovascular and respiratory disorders. More than 30% of adult individuals with asthma may show a slow HRR. Pulmonary rehabilitation improves exercise capacity in individuals with asthma or chronic obstructive pulmonary disease (COPD). Aim. To evaluate the effect of pulmonary rehabilitation on HRR in individuals with asthma as compared to those with COPD. Methods. Retrospective analysis of HRR un minute after the six-minute walking test (6MWT) before and after an exercise training program. COPD Assessment Test (CAT), Barthel Dyspnea Index (BId), Medical Research Council score (MRC) for dyspnea, and the Five Sit-to-Stand test (5STS) were also assessed as secondary outcome measures. Results. Slow HRR prevalence was significantly lower in individuals with asthma than with COPD (29.1% vs 46.7%, respectively: p=0.003). Post program HRR did not change in more than 70% of individuals in either population, improved in 16% of both populations, whereas HRR actually worsened in 12% and 10% of individuals with asthma and COPD respectively. The outcome measures significantly improved in both populations, irrespective of baseline HRR. Conclusion. In individuals with asthma or COPD exercise training does not significantly improve HRR.